ACONSELHAMENTO PASTORAL E A LEITURA POPULAR DA BÍBLIA: UM DIÁLOGO COM O PENSAMENTO DE CARLOS MESTERS - Souza, Priscila Leite de (2015)
This paper discusses the contributions of the Popular Reading of the Bible (PRB) with a view to Carlos Mesters for the care processes in Pastoral Counseling (PC). Critically rethinking the models of Pastoral Counseling (PC) from the main authors published in Brazil on the subject, it seems that the how to do pastoral counseling is fundamental As well as meditating on the how to use the Bible in the care and assistance cases in counseling should be directly related to knowing how to listen and discern the needs of others. Therefore, it is useful to integrate the reflection and practice of pastoral care, while counseling, the prospects of spirituality and human behavior sciences with the methodology of PRB. The PRB lends its hermeneutic view, judgement and acting and takes the Paulo Freires pedagogy in relational processes between advisor and advisee. This work intends to propose such a world reading that starts from the life lived taking into account age, ethnicity, socioeconomic status, marital status, gender, etc., in order to provide integral health to the human being. This type of comprehensive reading with the contributions of PRB can better promote the skills for listening that recognizes the relationships in Pastoral Counseling as an educational and liberating process between advisor and advisee. Process in which the contextualized, integral and liberating reading of the Bible and humanities light the way for a more humanizing life.